Asymmetric pass-through effects of oil price on economic growth in Malaysia - Bala, Umar; Lee, Chin; Maijama’a, Rabiu (Universiti Malaysia Sarawak, 2021)
This empirical analysis intends to examine the asymmetric response of economic growth when the oil price changes in Malaysia by applying threshold autoregressive (TAR) and momentum threshold autoregressive (MTAR) cointegration and asymmetric adjustment models. The results revealed that the oil price has an asymmetric impact on Malaysian economic growth. We found that when oil price increases this accelerates economic growth; however, the speeds of adjustment back to the steady position were insignificant. When the oil price dropped, oil price significantly and negatively affects economic growth for a period of time and then returns back to its normal position. The results revealed that Malaysian economic growth constantly benefits when the oil price increases and is temporarily negatively affected when oil prices drop. The results have important policy implications. This suggests that it is essential to the policy makers to consider different policy responses for hikes and drops in oil prices. The result implies that negative oil price shock would lower economic growth, however it is temporary. Therefore, policy makers might response by implementing expansionary monetary policy to stimulate economic growth. The explanation is intuitive. For example, an increase in the money supply would normally pull down the interest rate which would further encourage consumption and investment, stimulate economic growth, which would increase oil demand and push up its price.